PREVALENCE OF HYPOTHYROIDISM IN PATIENTS WITH HYPONATREMIA - SHABBIR, MA; RASHEEQ, T; HUSSAIN, I; TAHIR, M; NASIR, MS (Biological and Clinical Sciences Research Journal, 2023)
This study evaluated the prevalence of hypothyroidism in hyponatremic patients of varying severity. This prospective cross-sectional study was conducted at the Medicine department of Bakhtawar Amin Trust Hospital Multan from 19th March 2020 to 19th March 2021. Hospital registry data assessed the patient’s serum sodium, free thyroxine, and thyrotropin level. The study’s primary outcome was free T4 < 1.01 ng/dL and TSH > 10.0 μIU/mL. A total of 243 patients qualified to study criteria. Of them, 20 (8.2%) had overt hypothyroidism, and 50 (20.5%) had hypothyroidism. Hypothyroidism was categorized in terms of the Na levels such that six (12%) patients had Na >136mEq/L, 16 (32%) had Na=130-135mEq/L, and 28(56%) had Na < 129mEq/L. The number of patients with overt hypothyroidism in similar groups was two patients (10%), eight patients (45%), and 10 patients (50%), respectively. The rate of hypothyroidism increased significantly with an increase in the severity of hyponatremia (p<0.05). Multivariate logistic regression analysis on adjusting confounding factors revealed an increase in overt hypothyroidism rate with an increase in hyponatremia severity. Based on the results, overt hypothyroidism increases significantly with an increase in the severity of hyponatremia. The trend remains the same even after the adjustment of potential confounders.